Mechanical properties and microstructure of wire laser metal deposited austenitic stainless steel - P. Kyvelou; W. Hong; R. Zhang; L. Gardner (Materials & Design)
Laser metal deposition (LMD) is a metal 3D printing method that enables the efficient and cost-effective production of large-scale components, rendering it increasingly attractive for civil engineering applications. However, the scarcity of data and lack of knowledge of the material response and geometric variability of LMD steels is inhibiting adoption of this manufacturing method in the construction industry. To address this, a comprehensive experimental investigation into the geometry, mechanical properties and microstructural characteristics of LMD plates made from ER 308LSi stainless steel has been carried out and is presented herein. Laser scanning, tensile testing and microstructural analyses were conducted on a series of coupons of different thicknesses (2 mm and 8 mm), printing strategies, surface conditions and orientations. The results indicated low geometric irregularity, with both as-built and machined coupons displaying nearly identical mechanical properties. The thinner specimens had lower strengths, mainly attributed to their larger grain sizes. Significant anisotropy was observed from the mechanical tests on the thinner specimens, explained by a strong crystallographic texture observed in the microstructure. Overall, the examined material exhibited good mechanical behaviour and geometric consistency. Finally, a constitutive modelling approach previously applied to wire arc additively manufactured (WAAM) stainless steel was successfully adapted to characterise the anisotropic behaviour of LMD stainless steel in both the elastic and inelastic material ranges. The findings highlight the potential for using LMD in construction, offering a viable means of fabricating large-scale metal components with sound mechanical performance.